Neuromagnetic evidence that the right fusiform face area is essential for human face awareness: An intermittent binocular rivalry study. (August 2016) - Kume, Yuko; Maekawa, Toshihiko; Urakawa, Tomokazu; Hironaga, Naruhito; Ogata, Katsuya; Shigyo, Maki; Tobimatsu, Shozo
Highlights: We explored the initial steps of face awareness using MEG. Intermittent pseudo- and binocular rivalry conditions were used to record MEG responses. M130 and M170 were predominantly recorded in the right hemisphere. We found a significant difference in the M170 latency (human < monkey < house). M170 reflects the initial awareness of a human in the face fusiform face area. Abstract: When and where the awareness of faces is consciously initiated is unclear. We used magnetoencephalography to probe the brain responses associated with face awareness under intermittent pseudo-rivalry (PR) and binocular rivalry (BR) conditions. The stimuli comprised three pictures: a human face, a monkey face and a house. In the PR condition, we detected the M130 component, which has been minimally characterized in previous research. We obtained a clear recording of the M170 component in the fusiform face area (FFA), and found that this component had an earlier response time to faces compared with other objects. The M170 occurred predominantly in the right hemisphere in both conditions. In the BR condition, the amplitude of the M130 significantly increased in the right hemisphere irrespective of the physical characteristics of the visual stimuli. Conversely, we did not detect the M170 when the face image was suppressed in the BR condition, although this component was clearly present when awareness for the face was initiated. We also found a significant difference in the latency of the M170 (human < monkey < house). Taken together, our findings indicate that face stimuli are imperative for evoking the M170 and that the right FFA plays a critical role in human face awareness.